Effectiveness Counseling Technique Applied Thinking, Feeling, and Acting on Anxiety in Appendicitis Pre-Operating Patients - Sena Wahyu Purwanza; Cesario Tesa Priantoro; Fetreo Negeo Putra; Muhammad Rofi'i; Kurniawan Erman Wicaksono (Universitas Airlangga, 2024)
Introduction: Anxiety has been studied as the common finding in preoperative patients. For the most recent, nursing interventions aim to reduce anxiety were rely on counseling method. This study aims to determine the effectiveness of counseling applied thinking, feeling dan acting (TFA) on the level of anxiety in appendicitis pre-operative patients. Method: Anxiety has been studied as the common finding in preoperative patients. For the most recent, nursing interventions aim to reduce anxiety were rely on counseling method. This study aims to determine the effectiveness of counseling applied thinking, feeling dan acting (TFA) on the level of anxiety in appendicitis pre-operative patients. Results: Counseling by approach TFA on the level of anxiety in patients with pre-operation appendicitis with value p=0.000 or p < 0.05 which means it effectively reduces anxiety levels. Counseling applied thinking, feeling, and acting (TFA) effectively reduced the anxiety level of appendicitis pre-operative patients. Conclusions: Counseling with approach TFA on the level of anxiety in preoperative patients with appendicitis. Patients were able to express their feelings properly, have more rational thinking and prioritize useful actions so that anxiety can be reduced or even eliminated. Further studies should provide a comprehensive assessment of mechanisms anxiety realising in appendicitis pre-operative patients.